لانتقال من العدالة العقابية الى العدالة التقويمية لتاهيل المحبوس في التشريع الجزائري - بن لعريبي, راضية (جامعة الوادي University of Eloued, 2019)
رغم ما شمل المنظومة العقابية الجزائرية من تعديلات لا يزال الكثيرون يشككون في جدية هذه الأخيرة ودورها في إصلاح المحبوس والحد من الجريمة، لان الهدف في النهاية هو تحقيق الأمن والاستقرار داخل المجتمع والجريمة هي إحدى المشاكل التي تزعزع هذا الاستقرار، من اجل ذلك كان لزاما على الدولة الجزائرية أن تهتم بإصلاح المحبوس وإبعاده عن طريق العودة للانحراف من خلال الاهتمام بحقوق هذا الأخير واحترام كيانه كانسان والابتعاد عن كل أشكال التعذيب إضافة للاهتمام بالمؤسسات العقابية كمكان تنفذ فيه العقوبة السالبة للحرية هادفة بذلك لتحقيق عدالة عقابية، ولان العدالة العقابية لوحدها لا تكفي للإصلاح اتجهت مختلف التشريعات على غرار المشرع الوطني إلى العدالة التقويمية لتأهيل المحبوس معتمدة في ذلك على برامج تاهيلية مختلفة أثبتت نجاعتها في التشريعات المقارنة. Despite the fact that the Algerian penal system knew a lot of reforms, many still question the seriousness of this reforms and their role in redressing the prisoner and reducing crime. The goal of any penal system is to maintain security and stability within the community, and crime is one of the problems that undermine stability, that is why the Algerian State have to focus on reforming/redressing prisoners and keep them away from returning to deviation, this can only be done by preserving their rights and respecting their humanity and abolishing any form of torture in order to make the penal institutions a place of custody that ensure punitive justice; and since Penal Justice alone is not enough to redress prisoners, different legislations including the Algerian legislator opt for a correctional justice as a tool of rehabilitation by adopting different rehabilitation programs that proven their efficiency in comparative legislations.
moving From Punitive Justice To Correctional Justice In Prisoner Rehabilitation In The Algerian Legislation.
Keywords: العدالة العقابية، العدالة التقويمية، المحبوس، إعادة التأهيل; punitive justice, correctional justice, prisoner, rehabilitation